2004
DOI: 10.1016/j.jpaa.2003.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Extending Stone duality to multisets and locally finite MV-algebras

Abstract: Stone duality between boolean algebras and inverse limits of ÿnite sets is extended to a duality between locally ÿnite MV-algebras and a category of multisets naturally arising as inverse limits of ÿnite multisets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
70
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 24 publications
7
70
0
Order By: Relevance
“…Following the work in [7], it may be easily shown that the same dual equivalence between the categories C and MV lf defines a dual equivalence between the categories C * and MV * lf . Hence, it only remains to show that MV * lf is equivalent to WH lf , the category of locally finite Wajsberg hoops.…”
Section: Topological Duality For Locally Finite Wajsberg Hoopsmentioning
confidence: 97%
See 3 more Smart Citations
“…Following the work in [7], it may be easily shown that the same dual equivalence between the categories C and MV lf defines a dual equivalence between the categories C * and MV * lf . Hence, it only remains to show that MV * lf is equivalent to WH lf , the category of locally finite Wajsberg hoops.…”
Section: Topological Duality For Locally Finite Wajsberg Hoopsmentioning
confidence: 97%
“…In [7] the authors give a dual equivalence between the category of locally finite MValgebras and a certain category of multisets. We will see that the construction given in the previous section allows us to derive a topological duality for locally finite Wajsberg hoops by making minor changes to the corresponding duality for MV-algebras.…”
Section: Topological Duality For Locally Finite Wajsberg Hoopsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, see [28] for a Priestley style duality for MV and [6] for a duality for the class of locally finite MV-algebras.…”
mentioning
confidence: 99%